Forest Resources Exploitation and its Impact in the Extreme Salient of Java, 1870-1970 - Nawiyanto, Nawiyanto (TAWARIKH, 2015)
ABSTRACT: This article deals with the humanâs role in altering the environmental realities and the adaptation to the changing environment in the context of forest resources exploitation. The study is focused on a region of Java, called the Residency of Besuki, during the period of 1870-1970. The extraction of forest resources in the region had long taken place, but from circa 1870, it grew on an increasingly large scale. The growth was induced by the rising market demands for forest products and was facilitated by the gradually improved extraction technologies. Diverse products were taken from the regionâs forests to provide construction materials, firewoods, foodstuffs, and other requirements. The commercial extractions immediately led to a resource depletion and the small territorial size of the region made the possibilities of adopting a frontierâs exploit-and move-on attitude more limited. Under this constraint, adaptations were developed to adjust with the decline in forest resource supplies and to meet the challenges in securing the resources in demand by developing human-made production forests. This indicated that there was already interest in sustainable forest exploitation. The impact of the forest exploitation, however, was larger than being merely a matter of resource supplies. It also radically altered the regionâs environmental realities by replacing heterogenous natural forests with more homogenous human-made production forests. This change inevitably also led to the loss of the regionâs biodiversity richness.KEY WORDS: Environmental change, forest exploitation, human impact, colonial and early independence periods, Besuki residency, and Java island.About the Author: Dr. Nawiyanto is a Lecturer at the Department of History, Faculty of Letters UNJEM (University of Jember), Jalan Kalimantan No.37 Jember 68121, East Java, Indonesia. Corresponding author is available via e-mail at: snawiyanto@gmail.comHow to cite this article? Nawiyanto. (2015). âForest Resources Exploitation and its Impact in the Extreme Salient of Java, 1870-1970â in TAWARIKH: International Journal for Historical Studies, Vol.6(2) April, pp.149-168. Bandung, Indonesia: Minda Masagi Press and UNHAS Makassar, ISSN 2085-0980. Chronicle of the article: Accepted (August 31, 2014); Revised (December 19, 2014); and Published (April 28, 2015).